2018
DOI: 10.1016/j.joen.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combination of Intranasal Ketorolac and Nitrous Oxide on the Success of the Inferior Alveolar Nerve Block in Patients with Symptomatic Irreversible Pulpitis: A Prospective, Randomized, Double-blind Study

Abstract: Premedication with intranasal ketorolac did not significantly increase the odds of success for the IANB over the use of nitrous oxide/oxygen alone. Supplemental anesthesia will still be needed to achieve adequate anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Apart from oral administration, ketorolac has also been shown to be effective as buccal administration [ 23 ]. In contrast, adjuvant ketorolac with nitrous oxide has not been shown to have any additive analgesic effect in patients with symptomatic pulpitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from oral administration, ketorolac has also been shown to be effective as buccal administration [ 23 ]. In contrast, adjuvant ketorolac with nitrous oxide has not been shown to have any additive analgesic effect in patients with symptomatic pulpitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They selected a concentration of 30%–50% nitrous oxide in their study and reported that concentrations such as 70% would cause more side effects such as nausea and vomiting. Stentz et al [79] administered intranasal ketorolac before nitrous oxide sedation; however, this approach failed to make a significant improvement on IANB and the authors concluded that supplemental anesthesia would still be required.…”
Section: Discussionmentioning
confidence: 99%
“…has shown the effectiveness in the treatment of inflammation in oral cavity and sharp pain, when it was administered orally, buccally, parenterally and intranasally [7][8][9]. However, using the ketorolac trometamine in such dosage form as a dental film will allow providing targeted treatment of the affected areas, as well as to modify release and correct the intensity of the side effects.…”
Section: Development Of Composition and Technologies Of Dental Film Wmentioning
confidence: 99%